Euroland in crisis as the global meltdown picks up speed - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 2011)
Yet another rescue plan for the European Monetary Union (EMU) is making its way through central Europe, but no one is foolish enough to believe that it will be enough. Greece's finance minister reportedly said that his nation cannot continue to service its debt, and hinted that a 50 percent write-down is likely. That would be just the beginning, however, as other highly indebted periphery nations will follow suit. All the major European banks will be hit - and so will the 3 trillion US market for money market mutual funds, which have about half their funds invested in European banks. Add in other US bank exposure to Europe and you are up to a potential 3 trillion hit to US finance. Another global financial crisis is looking increasingly likely. We first summarize the situation in Euroland. Our main argument will be that the problem is not due to profligate spending by some nations but rather the setup of the EMU itself. We then turn to US problems, assessing the probability of a return to financial crisis and recession. We conclude that difficult times lie ahead, with a high probability that another collapse will be triggered by events in Euroland or in the United States. We conclude with an assessment of possible ways out. It is not hard to formulate economically and technically simple policy solutions for both the United States and Euroland. The real barrier in each case is political - and, unfortunately, the situation is worsening quickly in Europe. It may be too late already.
Keywords: E32; E42; F02; F33; 330; sovereign debt; PIIGS; European Monetary Union; global financial crisis; debt relief; sectoral balances; budget deficits; Fisher debt deflation; sovereign currency; greek default